Chemical constituents of the roots of Kniphofia schimperi and evaluation of their antimicrobial activity - Ebisa Mirete Deresa; Negera Abdissa; Dele Abdissa (Heliyon, 2024)
Kniphofia schimperi is one of the endemic plants of Ethiopia and is widely used for the treatment of microbial infections. However, the biological and phytochemical information pertaining to this plant has not been reported so far. Anticipated by these claims, the chromatographic isolation of the CHCl3/CH3OH (1:1 v/v) extract of the roots of K. schimperi afforded five compounds, viz., knipholone (1), asphodeline (2), β-sitosterol (3), 9-pentacosenoic acid (4), and nonacosanoic acid (5). The structures of the isolated compounds were identified based on their NMR (1D and 2D) spectral data analysis and comparison with reported literature data. The crude extract and isolated compounds were evaluated for their in vitro antimicrobial activity against four bacterial strains (Escherichia coli, Salmonella typhimurium, Staphylococcus aureus, and Bacillus cereus) and a fungal strain (Candida albicans) using the agar disk diffusion method. The test samples showed moderate antimicrobial activity, with the highest activity observed for compound 3 (with a zone of growth inhibition of 15.5 ± 0.71 mm) against S. typhimurium.